The Curved MCA: Influence of Vessel Anatomy on Recanalization Results of Mechanical Thrombectomy after Acute Ischemic Stroke - Schwaiger, B.J.; Gersing, A.S.; Zimmer, C.; Prothmann, S. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: Vessel anatomy is assumed to influence results of endovascular mechanical thrombectomy using stent retrievers. The purpose of this study was to analyze the influence of vessel curvature on recanalization results in patients with acute ischemic stroke caused by large-vessel occlusion. MATERIALS AND METHODS: In 159 patients (70 ± 12.8 years of age; 79 women) treated for acute ischemic stroke after carotid T and/or MCA occlusion by using stent retrievers, the following angles were measured in standard anteroposterior angiograms to describe vessel anatomy: first, between the terminal ICA segment and the most downward curved M1 segment conterminous to the proximal face of the thrombus (ICA/M1 angle); second, between the most proximal M1 segment and the segment immediately conterminous to the thrombus (M1/M1 angle); and additionally, in patients with distal M1/proximal M2 occlusion, the angle of the last curvature proximal of the thrombus (M1/M2 angle). Angles of patients with-versus-without successful recanalization were compared. RESULTS: Patients without successful recanalization (TICI 0–2a) showed significantly larger ICA/M1 angles (mean, 110°± 23.8° versus 69°± 28.7°, P < .001) and significantly larger M1/M1 angles (56°± 29.2° versus 29°± 26.6°, P = .001) than patients with successful recanalization (TICI 2b/3). In patients without successful recanalization after a distal M1 or proximal M2 occlusion, the M1/M2 angle was significantly larger than that in patients with successful recanalization (117° ± 34.3° versus 67° ± 29.5°, P = .006). CONCLUSIONS: This retrospective analysis showed that mechanical thrombectomy in the anterior circulation was significantly less often successful in patients with large vessel angles. Therefore, vessel curvature significantly influences the results of mechanical thrombectomy with stent retrievers for treatment of acute ischemic stroke. Further work is needed to understand the underlying causality. MTendovascular mechanical thrombectomyROCreceiver operating characteristic